Influence of van der waals interactions between the alkyl chains of surface ligands on the size and size distribution of nanocrystals prepared by the digestive ripening process - Shimpi, Jayesh R.; Thomas, Rinto; Meena, Santosh Kumar; Prasad, Bhagavatula L. V. (Langmuir, 2023)
Thermal heating of polydispersed nanocrystals (NCs) with surface-active organic ligands in a solvent leads to the formation of monodispersed NCs, and this process is known as digestive ripening (DR). Here, by performing DR on Au NCs using different-chain-length amine and thiol ligands, we evidently show that ligands with C-12 chain length result in the formation of NCs with narrow size distributions when compared to C-8, C-16, and C-20 chain length ligands. Furthermore, our findings also show that in the case of alkyl thiol, the NC size remains more or less the same, while the size distribution gets altered significantly with the chain length. On the other hand, both size and size distribution are affected significantly when the alkyl amine chain length is varied. Fourier transform infrared (FTIR) studies indicate that the van der Waals (vdW) interactions are weakest when the amine with C-12 carbon chain is used as the DR agent, while in the case of thiols, molecules with C-8 and C-12 chain lengths have nearly the same vdW interactions (with C-12 slightly weaker than C-8), which are weaker than those of C-16 and C-20. Molecular dynamics (MD) simulation results corroborate the experimental observations and suggest that due to more defects in the alkyl chain, the C-8 and C-12 (amine as well as thiol) ligands are disordered and less stable on Au(111) and Au(100) surfaces. This could result in efficient etching and redeposition, making the ligands with C-8 and C-12 chain lengths the better DR agents.